Incidence and risk factors of spondylolysis in youth football: a longitudinal study among male Norwegian players - Morland, N.; Tovi, D.; Clarsen, B.; Rygh, C. B.; Bache-Mathiesen, L. K.; Clemm, H. H.; Gundersen, H. (BMJ Open Sport & Exercise Medicine, 2026)
Objectives Spondylolysis is a common source of low back pain (LBP) among adolescent athletes. We aimed to investigate the occurrence of LBP and spondylolysis, and the potential associations of weekly training and match exposure, and maturity status with spondylolysis among male youth football players.